UJI ANTIBAKTERI PERASAN AKAR BAYAM DURI (Amaranthus spinosus Linn) TERHADAP Shigella dysenteriae - Ariana, Diah (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST)
UJI ANTIBAKTERI PERASAN AKAR BAYAM DURI (Amaranthus spinosus Linn) TERHADAP Shigella dysenteriaeDiah Ariana, S.T. M.Kes.Prodi D3 Analis Kesehatan UM Surabayadiahariana0101@gmail.comÂ ABSTRACTShigella dysenteriae is a bacterial pathogen that causes shigellosis causes severe diarrhea, prolonged, and fatal compared with diarrhea caused by other Shigella. The use of antibacterial drugs in the form of synthetic chemistry with a long period of time can cause side effects such as allergic reactions, asthma, and indigestion. Thorny Amaranth Root (Amaranthus spinosus Linn) is one of the traditional herbs that can be used as a natural antibacterial against Shigella dysenteriae because it contains flavonoids, alkaloids, and tannins so that the plants do not cause side effects.The formulation of the problem of this research is there any effect of freshly squeezed Thorny Amaranth Root (Amaranthus spinosus Linn) against Shigella dysenteriae. The purpose of this study to investigate the effect and the optimum concentration Thorny Amaranth Root juice (Amaranthus spinosus Linn) against Shigella dysenteriae. This type of research is experimental with a total of 28 samples consisting of 7 concentrations, ie 0%, 50%, 60%, 70%, 80%, 90% and 100% and 4 repetitions. This research is conducted in the Laboratory of Microbiology Prodi D3 Health Analyst Faculty of Health Sciences, University of Muhammadiyah Surabaya for 3 days. Using a dilution method by observing the presence or absence of bacterial growth. Analysis of data using ANOVA test with an error rate of 5% (0.05). And advanced test using test Tukeys Honest Significant Difference (Tukeys HSD). The final conclusion is that there is influence Thorny Amaranth Root (Amaranthus spinosus Linn) against Shigella dysenteriae. After testing Tukeys HSD obtained Minimum inhibitory concentration (MIC) is 80%.Â Keywords: Shigella dysenteriae, Amaranthus spinosus Linn